Ferrocene/ferrocenium redox shuttling: Peroxide decomposition catalysis applied to vinyl monomers polymerization under suspension conditions. (8th November 2022) - Zouhri, Yassir; Berthé, Jean-Michel M.; Bonnet, Fanny; Stasik, Bernard; Colemonts, Christel; Lasuye, Thierry; Mortreux, André; Champouret, Yohan; Visseaux, Marc
Abstract: Ascorbic acid derivatives in combination with ferrocenyl-based activators in catalytic amounts, referred to as kickers, are described as powerful redox systems to promote the decomposition of organic peroxides into radicals for the polymerization of vinyl monomers under suspension conditions. According to the nature of both the vinylic monomer and the peroxide, the initial polymerization rates can be improved by a factor up to 8. In the presence of ferrocene/ascorbyl palmitate kicker, the overall polymerization time of VCM was reduced from 3 to 2 h under industrial conditions. However, crusting during polymerization as well as yellowing of PVC upon thermal tests were observed. The first problem was solved by changing the surfactant, while optimizing the injection mode of the kicker improved the efficiency of the process without affecting the quality of the resulting PVC. This study demonstrates the effectiveness of ferrocene-based kickers in improving the polymerization of vinyl monomers under suspension conditions. Graphical abstract: Image 1 Highlights: Ferrocene-based kickers are described as powerful redox catalysts towards di(2-ethylhexyl)peroxydicarbonate) and lauroyl peroxide decomposition under suspension conditions. Significant improvement of energy efficiency in vinyl monomers polymerization including vinyl acetate, methyl methacrylate and vinyl chloride. When applied to vinyl chloride in suspension under industrial conditions, the overall polymerization time is reduced from 3 to 2 h.